Application of Computational Thinking as an Effort to Optimize Business Processes in Samudera Motor Showroom Sales - Eunike Octavia Nababan; Nasywa Rakha Arrafi; Agnes Kurnia Gulo; Fawwaz Nabila Zulanifa; Nabila Zulanifa; Karina Ghaisani; Adinda Nuril Ashfiya; Nindy Irzavika (novamindpress, 2025)
The integration of computational thinking into the sales workflow of Samudera Motor provides significant opportunities for optimizing business processes. Through decomposition, key issues were identified clearly; pattern recognition highlighted recurring operational inefficiencies; abstraction helped isolate essential system components; and algorithm design produced structured solutions that can be implemented digitally. These findings demonstrate that computational thinking offers both a theoretical and practical framework for transforming traditional manual workflows into efficient, data-driven, and customer-oriented business processes. Implementing the proposed solutions can enhance operational accuracy, streamline decision-making, and significantly improve customer service performance at Samudera Motor. Furthermore, the application of computational thinking in the vehicle sales process provides an innovative foundation for enhancing efficiency and responsiveness to customer needs. By applying decomposition, pattern recognition, abstraction, and algorithm design, the study successfully identified major challenges in the manual sales workflow, such as difficulty in tracking sales history, lack of system integration, and a high risk of data errors. Proposed recommendations including data entry automation, the use of barcode or RFID technology, data analytics for identifying purchasing trends, and the development of an integrated centralized system are expected to improve operational efficiency, enrich customer experience, and support more adaptive sales strategies. Computational thinking serves not only as an analytical tool but also as a foundation for comprehensive business transformation, strengthening the competitiveness and long-term sustainability of Samudera Motor's showroom operations amid an increasingly dynamic market landscape.